2017
DOI: 10.1111/mcn.12422
|View full text |Cite
|
Sign up to set email alerts
|

Is competence enough to enable Kenyan mothers to make good infant and young child feeding decisions?

Abstract: The aim of this study was to explore factors associated with maternal infant and young child feeding motivation in urban and rural Kenya. We conducted 18 focus group discussions with mothers of children 0 to 23 months of age and healthcare workers. The data were transcribed, translated, and explored following the principles of content analysis. We first explored and coded the data inductively and categorized it according to emerging themes representing the most relevant topics for young child feeding. After th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
4
0
2
Order By: Relevance
“…Ibu harus didukung oleh dukungan sosial yang lebih tinggi seperti dari pekerja kesehatan komunitas yang berkompeten untuk memberikan edukasi dan nasihat mengenai praktik makan bayi dan anak. 8 Di Thailand, penurunan prevalensi kurang energi-protein terjadi secara signifikan karena akses terhadap pelayanan kesehatan dan program gizi berbasis komunitas yang efektif. 9 Sejumlah penelitian intervensi terhadap gizi balita telah dilakukan di beberapa daerah di Indonesia.…”
Section: Action: Aceh Nutrition Journal November 2020 157unclassified
“…Ibu harus didukung oleh dukungan sosial yang lebih tinggi seperti dari pekerja kesehatan komunitas yang berkompeten untuk memberikan edukasi dan nasihat mengenai praktik makan bayi dan anak. 8 Di Thailand, penurunan prevalensi kurang energi-protein terjadi secara signifikan karena akses terhadap pelayanan kesehatan dan program gizi berbasis komunitas yang efektif. 9 Sejumlah penelitian intervensi terhadap gizi balita telah dilakukan di beberapa daerah di Indonesia.…”
Section: Action: Aceh Nutrition Journal November 2020 157unclassified
“…Past studies evaluating women's behavior toward IYCF practices in Kenya have focused on variety of factors, including socioeconomic aspects, with attention to HIV-AIDS status of mothers (Dasgupta et al 2017;Gewa and Leslie 2015;Kimani-Murage et al 2013;Wanjiku et al 2015;Wanjohi et al 2017); community level factors including access to health care facilities and community worker's incentive system (Nguyen et al 2016); parental role in decision-making and care practices (Chintalapudi et al 2017); intrahousehold factors including caregivers' competence (Schneider et al 2017) and the policy environment (Sanghvi et al 2016). Further, Issaka, Agho, and Renzaho (2017), Habtewold, Islam, and Sharew et al (2017), and Ogbo, Page, and Idoko et al (2015) use meta-analysis to examine the effect of multiple factors on IYCF.…”
Section: Introductionmentioning
confidence: 99%
“…Over 95% of the mothers in our study knew that babies should get only breastmilk during their first 3 days; however, 10% of the children in Nairobi and 14% in Machakos were given pre-lactal feeds. Focus group discussions revealed that Kenyan mothers had little decision-making power during and after childbirth (Schneider et al, 2017), which may be the case in the current study. Nurses in South Africa were reported to give both pre-lactal feeds and advice that did not support exclusive breastfeeding (Jama et al, 2017).…”
Section: Discussionmentioning
confidence: 99%